Feasibility Study of a Small Animal PET Insert Based on a Single LYSO Monolithic Tube - Gonzalez, Antonio J.; Berr, Stuart S.; Cañizares, Gabriel; Gonzalez-Montoro, Andrea; Orero, Abel; Correcher, Carlos; Rezaei, Ahmadreza; Nuyts, Johan; Sanchez, Filomeno; Majewski, Stan; Benlloch, Jose M. (Frontiers in Medicine, 2018)
There are drawbacks with using a Positron Emission Tomography (PET) scanner design employing the traditional arrangement of multiple detectors in an array format. Typically PET systems are constructed with many regular gaps between the detector modules in a ring or box configuration, with additional axial gaps between the rings. Although this has been significantly reduced with the use of the compact high granularity SiPM photodetector technology, such a scanner design leads to a decrease in the number of annihilation photons that are detected causing lower scanner sensitivity. Moreover, the ability to precisely determine the line of response (LOR) along which the positron annihilated is diminished closer to the detector edges because the spatial resolution there is degraded due to edge effects. This happens for both monolithic based designs, caused by the truncation of the scintillation light distribution, but also for detector blocks that use crystal arrays with a number of elements that are larger than the number of photosensors and, therefore, make use of the light sharing principle. In this report we present a design for a small-animal PET scanner based on a single monolithic annulus-like scintillator that can be used as a PET insert in high-field Magnetic Resonance systems. We provide real data showing the performance improvement when edge-less modules are used. We also describe the specific proposed design for a rodent scanner that employs facetted outside faces in a single LYSO tube. In a further step, in order to support and prove the proposed edgeless geometry, simulations of that scanner have been performed and lately reconstructed showing the advantages of the design.